Social Responsibility and Sustainability from the Customer’s Perspective in a Hotel in Lima, Peru - Collado-Calenzani, Maria Hilda; Ríos-Lama, Cristian Armando; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
This research aimed to determine the relationship between Corporate Social Responsibility and Sustainability from the customer’s perspective in a Miraflores hotel in the year 2023. Methodologically, the study adopted a quantitative approach, non-experimental design, cross-sectional, and simple correlational design. The sample consisted of 80 customers from a Miraflores hotel. The technique of direct or face-to-face interviews was used to collect information through a questionnaire for each variable, validated by experts in the field. The obtained Cronbach’s Alpha of 0.91 indicates high statistical reliability. The results confirm a positive and significant relationship between Corporate Social Responsibility and Sustainability. The Spearman test verifies its significance, which is < 0.001, with a correlation coefficient of 0.636. It is concluded that the proper business management of the hotel, implemented in four dimensions: ethical, philanthropic, legal, and economic, related to Sustainability, generates competitiveness, enhances the corporate image, contributes to environmental conservation, attracts more customers, and achieves a return of higher profits.